Current Diagnosis and Management of Thyroid Nodules - Tjokorda Gde Dalem Pemayun (Interna Publishing, 2016)
Thyroid nodules are frequently found. Although they are often palpable, many are found incidentally during unrelated radiographic studies. Ten to 15% of thyroid nodules represents thyroid malignancy. Clinician suc as an internist/endocrinologist have to  classify the nodule, stratify the risk of thyroid cancer, performed a diagnostic work-up, provide medical / non-surgical therapy, select candidates for surgery and provide appropriate follow-up that should last a lifetime. This article provide an up-date review of diagnostic approach and management of thyroid nodules, focusing on current algorithm in lights of the most recent published American Thyroid Association thyroid nodule and differentiated thyroid cancer management guidelines.